ECOLOGICAL PERFORMANCE ANALYSIS OF IRREVERSIBLE OTTO CYCLE - Ust, Yasin (YILDIZ TECHNICAL UNIV, 2005)
In this paper, a comparative performance analysis and optimization based on the power output, ecological objective function and ecological coefficient of performance (ECOP) criteria have been performed for an air-standard irreversible internal combustion engine Otto cycle coupled to constant temperature heat reservoirs. A detailed numerical study has been done by considering the finite-rate heat transfer irreversibilities, heat leakage and internal irreversibilities. The obtained results are compared with those of the maximum ecology and maximum power criterion. The results showed that the Otto cycle operating under maximum ECOP conditions has important advantageous in terms of entropy generation rate and thermal efficiency.
Keywords: Otto cycle; Optimization; Irreversible; Ecological performance; Engineering